Reinforced Concrete Columns with Local Prestressing Rebars: A Calculation Theory and an Experimental Study - Anton Chepurnenko; Andrei Lipovich; Alexey N. Beskopylny; Besarion Meskhi (Buildings, 2022)
Local prestressing of reinforcement can be effective for slender reinforced concrete columns with large longitudinal force eccentricities. This article deals with columns with prestressed reinforcement on the side opposite to the eccentricity of the longitudinal force. Prestressing is created with the help of turnbuckles. The aim of the work is to develop a model for determining the stress–strain state of columns with local prestress and its experimental verification. The article presents the derivation of a resolving equation for the increment of deflection, which considers the non-linearity of the concrete and reinforcement work, the presence of creep and shrinkage of concrete. The solution of the resulting equation was performed numerically by the finite difference method in a MATLAB environment. Experimental studies were carried out according to the hinged support scheme for eight eccentrically compressed samples, four of which had been prestressed. Experiments and numerical modeling of columns with local prestressing showed a significant increase in crack resistance (by 1.3–2.5 times) and bearing capacity (by 12.5–30%) compared to similar structures without prestressing.